Diversity and Inclusion in the Nigerian Work Environment: Opportunities and Challenges - NWAKANMA, Chinegbonkpa Hope (Universitas PGRI Madiun, 2024)
The Nigerian work environment reflects the nation's kaleidoscope of cultures, ethnicities, languages, and religions. However, the importance of leveraging this robust diversity and achieving an inclusive workplace is rarely researched. Using the thematic literature review method, this paper explores the complex diversity and inclusion landscape in the Nigerian work environment, focusing on the opportunities it offers for growth, the challenges to overcome to harness these opportunities and the policies for addressing the issues of diversity and inclusion. Findings revealed that diversity and inclusion attract top talent, enhance innovation, corporate performance, and decision-making, and reduce biases, stereotypes, and employee attrition. It also revealed complex challenges, including change resistance, hidden biases, and communication barriers. Organisations can navigate these challenges by employing diversity training, inclusive leadership, equal opportunity, and general language policies. A contradiction was also revealed between the country’s ability to utilise its diverse potential and what is being achieved resulting from a low level of equity and inclusion in the Nigerian workplace and inadequate institutional and governmental structure to address the issues of inequality and discrimination. It is, therefore, imperative to formulate policies with broader coverage, expand existing ones and strengthen enforcement mechanisms to ensure compliance from both organisations and individuals. Keywords: Diversity, inclusive workplace, inequality, discrimination, Nigerian Work environment